The economic decision of international migration: Two empirical evidences from the United States and Canada - Jiyoung Park; Seong-woo Lee; Jonghoon Park (Economies, 2024)
This study investigated whether economic motivations are a key factor in international migration decisions. Applying the selectivity-corrected expected income for migrants and stayers, the difference in expected income for an individual in origin and destination countries was analyzed. This study used data from the U.S. and Canada to empirically test the role of income gaps in migration decisions. The main difficulty in analyzing the role of the gaps lies in collecting both income streams for the same individual, since once an individual migrates to a different country, their potential income in the origin country cannot be observed; and vice versa for stayers. Therefore, directly applying the average income of migrants (conditionally relying on their observed characteristics) to estimate the income of stayers if they had migrated results in a biased estimate of stayers' income. Hence, there is a need to account for selectivity in the migration decision and calculate selectivity-corrected income. The key finding in this study is that the expected income gap is positively associated with, and statistically significant for, international migration decisions for the U.S. and Canada. One of the main reasons may be the easy transfer of labor skills between countries that have similar labor environments and cultural backgrounds.
Keywords: 330; expected income difference; international migration; neoclassical economics; self-selection